All fours - July, Miranda 1974- (Riverhead Books, 2024)
"A semi-famous artist announces her plan to drive cross-country, from LA to NY. Twenty minutes after leaving her husband and child at home, she spontaneously exits the freeway, checks into a nondescript motel, and immerses herself in an entirely different journey. Miranda July's second novel confirms the brilliance of her unique approach to fiction. With July's wry voice, perfect comic timing, unabashed curiosity about human intimacy, and palpable delight in pushing boundaries, All Fours tells the story of one woman's quest for new kind of freedom. Part absurd entertainment, part tender reinvention of the sexual, romantic, and domestic life of a forty-five-year-old female artist, All Fours transcends expectation while excavating our beliefs about life lived as a woman. Once again, July hijacks the familiar and turns it into something new and thrillingly, profoundly alive."--
Keywords: Psychological fiction; Novels; Fiktionale Darstellung